The Influence of School Principals' Learning Leadership and School Climate on Teacher Performance - Alnisyar, A. Aulia Reski Novianti; Fatmiati Nur (Universitas Nahdatul Ulama Surabaya, 2024)
A good school is supported by the leadership role of the principal, the performance of all stakeholders and the school climate. Based on this, the researcher took the role of learning leadership as the object of research because the researcher considers that the leadership role of the school principal is considered capable of improving the quality of education and creating a conducive school atmosphere, not only carrying out his duties and functions as a school leader. This research focuses on the principal's instructional leadership, teacher performance and school climate. The aim of the research is to find out whether learning leadership and school climate can influence teacher performance. The method used is quantitative research. Data was collected by distributing questionnaires and processed using the SPSS application. Data analysis used multiple regression analysis, partial analysis, simultaneous analysis and coefficient of determination analysis. The research location was Makassar City Public High School, Manggala District using simple random sampling so that the research sample was 140 people (teachers). The results of the research show that in partial tests and simultaneous tests, the principal's learning leadership and school climate influence teacher performance. The successful management of learning leadership carried out by the principal and the creation of a school climate has an impact on teacher performance in teaching, where the principal has sharp intuition, transfers the mission and goals of the school, increases efficiency and a comfortable and safe environment supported by positive conditions